Effects of narcissism in essential workers during COVID-19. (March 2021) - Freis, Stephanie D.; Brunell, Amy B.
Abstract: We studied essential workers during the COVID-19 pandemic. We hypothesized that trait narcissists would communicate more about their work during the pandemic because their work elevated their status to "hero" and provided an opportunity to shine. We found evidence of this for grandiose, but not vulnerable narcissism. Second, we hypothesized that sharing about work would be associated with increases in state narcissism. Results supported this for state grandiose narcissism with mixed evidence for state vulnerable narcissism. Perceiving validation from others was associated with higher state grandiose narcissism and self-esteem, as well as lower vulnerable narcissism in one sample.